Ethical Issues at the Interface of Physiotherapy Care and Research Practice in Pediatric Oncology-Descriptive Study - Malarvizhi D1 , Metha K S2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Pediatric oncology has a major role in research. This paper discuss about the ethical consequences ofphysiotherapy care and research in Pediatric Oncology. Empirical ethics is a broad division,grasping,difference in indicatingethics and empirical research. A major Australian tertiary teaching hospital revealsthat 65 % of patient presents with specific indication for physiotherapy, in that only12.8% are receivingphysiotherapy. Indications includes in physiotherapy care are pain, lymph- oedema, incontinence, respiratoryand musculoskeletal Problems also it includes hard to move. Physiotherapy has extensive role inpalliativeoncology, it also has large preventative ,educative and supportive roles to play and provides independentand complementary therapies for physical debility and pain. Pain from reflex spasm and contracture aredealt with Physiotherapists. Founded that no reference based on standard of life and quality-adjusted lifeyears in terms of preventing dependance and avoid hospitalisation. Treatment of pediatric oncology oftenhas physically, socially and psychologically demands. Always there must be some ethical reason for allthe decision on treatment and care for a patient with cancer. It is a fact that ethics needs not only all thestakeholders to do the right things but also it needs the one who do it in the right way. Research practice hasled us to great advances in pediatric oncology and the proportion is greater in children than adults. Obtainingthe informed consent and assent was the most important ethical challenges faced during the research.